Self-Propagating High Temperature Synthesis of TiB2–MgAl2O4 Composites; Metals; Vol. 7, iss. 8 - Radishevskaya N. I. Nina Ivanovna; Lepakova O. K. Olga Klavdeevna; Karakchieva N. I. Nataljya Ivanovna; Nazarova A. Yu. Anastasiya Yurjevna; Afanasjev N. I. Nikolay Ivanovich; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Gusev A. A. Aleksandr Anatoljevich (2017, 2017)
Title screen